A Status-Seeking Account of Psychological Entitlement. (July 2019) - Lange, Jens; Redford, Liz; Crusius, Jan
We propose that people high in entitlement are characterized by motivation to attain status. Five studies (total N = 2, 372) support that entitlement promotes motivation to seek status. This motivation, in turn, relates to affective processes when facing upward comparisons and contributes to status attainment. Specifically, entitlement fostered prestige and dominance motivation. These, in turn, predicted greater benign and malicious envy, respectively, when encountering high-status others. The indirect effects occurred when entitlement was measured (Studies 1A and 1B) and manipulated (Studies 2A and 2B). Finally, entitlement related to status attainment, yet not always in line with more entitled people's motivation. Although they ascribed themselves both more prestige and dominance, others ascribed them only more dominance, yet less prestige (Studies 3A, 3B, and 3C). These findings suggest that a status-seeking account offers important insights into the complexities of entitled behavior and its social consequences.